A reversible hydrogen storage material of Li-decorated two-dimensional (2D) C4N monolayer: First principles calculations. (21st September 2021) - Zhang, Yafei; Liu, Pingping; Zhu, Xiaoling; Liu, Ze
Abstract: Two-dimensional (2D) materials can be regarded as potential hydrogen storage candidates because of their splendid chemical stability and high specific surface area. Recently, a new dumbbell-like carbon nitride (C4 N) monolayer with orbital hybridization of sp 3 is reported. Motivated from the above exploration, the hydrogen adsorption properties of Li-decorated C4 N monolayer are comprehensively investigated via first principles calculations based on the density functional theory (DFT). It is found that the Dirac points and Dirac cones exists in the Brillouin zone (BZ) from the calculated electronic structure and indicates the C4 N can be used as an excellent topological material. Also, the calculated phonon spectra demonstrate that the C4 N monolayer owns a strong stability. Moreover, the calculated binding energy of decorated Li atom is bigger than its cohesive energy and results in Li atoms disperse over the surface of C4 N monolayer uniformly without clustering. In addition, the Li8 C4 N complex can capture up to 24H2 molecules with an optimal hydrogen adsorption energy of −0.281 eV/H2 and achieves the hydrogen storage density of 8.0 wt%. The ab initio molecular dynamics (AIMD) simulations suggest that the H2 molecules can be desorbed quickly at 300 K. This study reveals that Li-decorated C4 N monolayer can be served as a promising hydrogen storage material. Highlights: The 3D band structure clearly indicates the Dirac cones exist in the Brillouin zone of C4 N structure. Li-decorated C4 N monolayer can significantly improve the adsorption ability of H2 molecules. The hydrogen storage capacity achieves to 8.0 wt% and meets the target of DOE by the year 2025. H2 molecules can be quickly released at room temperature of 300 K.